1998
DOI: 10.1007/s002800050829
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and pharmacological specificity of dUTPase-mediated protection from DNA damage and cytotoxicity in human tumor cells

Abstract: We conclude that the role of uracil misincorporation and subsequent DNA damage in cytotoxicity induced by TS inhibitors, in HT29 cells, is time dependent, and that cytotoxicity caused by long-term exposure to these drugs is largely independent of resultant DNA damage, in this cell line. The inability of dutE to protect HuTu80 cells from FdUrd further suggests that the significance of uracil misincorporation resulting from TS inhibition varies among cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
4
14
0
Order By: Relevance
“…At a dose of 10 μM FdUrd, survival was 19% (±3.5, n=3) for the UNG proficient cells and 36% (±11.2, n=3), a less than 2-fold difference that was insignificant. It is known that elevated dUTPase expression can influence cell death caused by TS inhibitors [18][19][20][21]. The results in Figure 4 show that nuclear dUTPase protein levels are similar in the UNG proficient and UNG-inhibited cells.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…At a dose of 10 μM FdUrd, survival was 19% (±3.5, n=3) for the UNG proficient cells and 36% (±11.2, n=3), a less than 2-fold difference that was insignificant. It is known that elevated dUTPase expression can influence cell death caused by TS inhibitors [18][19][20][21]. The results in Figure 4 show that nuclear dUTPase protein levels are similar in the UNG proficient and UNG-inhibited cells.…”
Section: Resultssupporting
confidence: 55%
“…The formation of DNA double strand breaks has been reported following TS inhibition, although double strand breaks have not uniformly correlated with death in response to folatebased TS inhibitors [20,22]. We previously found that RTX induced sister chromatid exchanges at subtoxic doses, which suggested that homologous recombination was invoked during thymidylate deprivation [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acting as a competitive inhibitor, FdUTP could effectively tie up the enzyme, allowing dUTP pools to build up. Several studies have shown that dUTPase plays an important role in the sensitivity of a cell to thymidylate synthase inhibition (7)(8)(9)35). Expression of this enzyme has been shown to vary widely in tumor tissue.…”
Section: Discussionmentioning
confidence: 99%